Applying Meta-Ethical Methodology to the Study of Buddhist Ethical Terminology - Munkhtseren, Zolzaya (Mongolian Journal of Applied Linguistics, 2025)
In the 20th century, analytical philosophers began to study the ontology, epistemology, and logic of words and concepts expressing moral relation and values. In this context, it is necessary to carefully study the terms in Buddhist ethics. Therefore, in this paper, the importance of metaethical methodology is considered the translation and usage of Buddhist ethical terms. Recently, Buddhist scholars studying Buddhist views from the perspective of metaethics, but it expressed fewer that the problems of practical application of the terms in the Mongolian Buddhism. So, the author try to consider the applying method of methodology of meta-ethics to Buddhist ethics, and examples of the some Buddhist terms definition and translation from Mongolian commentary of "Bodhicaryāvatāra" written by Shantideva. Буддын ёс зүйн нэр томьёоны судалгаанд мета ёс зүйн арга зүйг хэрэглэх нь Хураангуй: ХХ зуунд аналитик философичид ёс суртахууны харилцаа, үнэлэмжийг илэрхийлсэн категори, ухагдахууны онтологи, эпистемологи, логикийн асуудлыг судлах болсон юм. Энэ хүрээнд шашны ёс зүйн нэр томьёоны асуудал ч хамаарна. Сүүлийн үед өрнийн буддын судлаачид мета ёс зүйн үүднээс буддын үзэл санааг судлах болсон хэдий ч буддизм дэлгэрсэн орнуудад буддын ёс зүйн нэр томьёоны хэрэглээ ямар түвшинд буйг харьцуулсан судалгаа хомс байна. Мета ёс зүйн арга зүй нь буддын мэдлэг ухааныг шинжлэх ухааны нэр томьёо судлалын үүднээс авч үзэхэд чухал юм. Иймээс мета ёс зүйн арга зүйг буддын ёс зүйн судалгаанд харгалзах онол, арга зүйн зарим асуудал хийгээд Шантидэва гэгээний айлдсан «Бодьсадвын явдалд орохуй» шастирын тайлбар зохиолоос зарим нэр томьёоны оноолт, орчуулгыг жишээгээр харуулахыг зорьсон болно. Түлхүүр үг: ёс суртахууны хэл, мета онол, аналитик философи, мета илэрхийлэл